2020
DOI: 10.1101/2020.12.15.20248251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk of Stress/Depression and Functional Impairment in Denmark Immediately Following a COVID-19 Shutdown

Abstract: Background This study aimed to investigate the impact of the first COVID-19 lockdown (March-April 2020) on risk for stress/depression and functional impairment in a representative sample of adult individuals in Denmark, and whether the impact of lockdown was heterogeneous across living situation. Methods: Using a representative, randomly drawn sample from the complete Danish adult population interviewed in March 2 to April 13, 2020 (n=2,836) and again in July 2020 (n=1,526, 54% retention rate), we study how t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…This could lead parents or physicians to rate children to have more symptoms now compared to in pre-pandemic years. Increased family time during the pandemic [16] could make parents more responsive to their children's symptoms. If fears of contracting COVID-19 or overburdening the healthcare system increased the threshold for seeking help, the worsening of mental health would be larger than the increase in consultations suggest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could lead parents or physicians to rate children to have more symptoms now compared to in pre-pandemic years. Increased family time during the pandemic [16] could make parents more responsive to their children's symptoms. If fears of contracting COVID-19 or overburdening the healthcare system increased the threshold for seeking help, the worsening of mental health would be larger than the increase in consultations suggest.…”
Section: Discussionmentioning
confidence: 99%
“…All models control for (or are estimated separately by) sex (female = 1, male = 0) and age category (ages 6-12, 13-15, and [16][17][18][19], which corresponds to the age of enrollment in primary, secondary, and high school. We also report analyses stratified by the capital area (counties Oslo and Viken) versus all other geographic regions in Norway.…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stay-at-home orders and suggestions following the coronavirus disease 2019 (COVID-19) pandemic have caused substantial changes to everyday life for families, who quite literally are stuck at home together. Although findings on the impact of the pandemic and the measures governments have used to counter it on mental health and relationship quality are mixed (e.g., Andersen, Fallesen, and Bruckner 2020; Kowal et al 2020; Mari et al 2020), concerns have been raised on the impact of stay-at-home orders for couples in general (Luetke et al 2020; Pietromonaco and Overall forthcoming; Stanley and Markman 2020) and couples with higher levels of conflict in particular (Lebow 2020; Pieh et al 2020; Zhang forthcoming). On one hand, pandemic-induced stress and anxiety may increase levels of conflict.…”
mentioning
confidence: 99%
“…A rapidly growing literature has investigated the effects of the COVID-19 pandemic and its associated societal lockdowns on populations’ mental health. Most of the findings from these studies indicated that the pandemic and associated societal lockdowns and periods of social isolation contributed to increased levels of loneliness, depression, and anxiety 1 8 , while a few studies examining changes in mental health indicated that some mental health outcomes improved, stayed the same, or worsened only slightly, compared to pre-pandemic years 9 11 . Considering that a national lockdown is one of the most effective non-pharmaceutical interventions to reduce the spread of COVID-19 and related deaths 12 , it is of utmost importance to understand which factors during a lockdown may lead to adverse psychological effects.…”
Section: Introductionmentioning
confidence: 99%